2014
DOI: 10.3390/ijerph110202148
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Mapping Spatial Associations among Oral Cancer Mortality Rates, Concentrations of Heavy Metals in Soil, and Land Use Types Based on Multiple Scale Data

Abstract: In this study, a deconvolution procedure was used to create a variogram of oral cancer (OC) rates. Based on the variogram, area-to-point (ATP) Poisson kriging and p-field simulation were used to downscale and simulate, respectively, the OC rate data for Taiwan from the district scale to a 1 km × 1 km grid scale. Local cluster analysis (LCA) of OC mortality rates was then performed to identify OC mortality rate hot spots based on the downscaled and the p-field-simulated OC mortality maps. The relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Recently, it has been reported that environmental exposure to heavy metals is an important risk factor for developing oral cancer, with studies on animals showing that chronic intake of chromium (Cr) could induce oral cancer [27]. Another spatial association between soil heavy metal content and oral cancer incidence and mortality has also been assessed in Taiwan [19,28]. Moreover, a study conducted in Brazil by Moi et al (2018), showed the consumption of pesticides, and HPV contamination, positively correlated with mortality rates from oral cancer in adults [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that environmental exposure to heavy metals is an important risk factor for developing oral cancer, with studies on animals showing that chronic intake of chromium (Cr) could induce oral cancer [27]. Another spatial association between soil heavy metal content and oral cancer incidence and mortality has also been assessed in Taiwan [19,28]. Moreover, a study conducted in Brazil by Moi et al (2018), showed the consumption of pesticides, and HPV contamination, positively correlated with mortality rates from oral cancer in adults [26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Population-Weighted Average, local and global Empirical Bayes and Poisson Kriging have been used to estimate disease-specific mortality rates from age-adjusted data. Accounting for spatial correlation patterns for low and high frequency rates, Poisson Kriging have shown better results [ 59 , 60 ]. Kriging methods allow to estimate spatial risk considering heterogeneity among small areas from poorly reported databases [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…where 1000 is the number of realizations, and ( ) is the number from the 1000 realizations in which the simulated species were present at location k. The joint probability (Pj, global uncertainty) in m occurrence locations ( , , , ⋯ ) was written as follows [63,64]:…”
Section: Variability Analysismentioning
confidence: 99%